A study on the neonatal outcomes of elective caesarean section comparing before and after 39 weeks in Hospital Sultanah Nurzahirah, Kuala Terengganu - Yaacob, Nazian Hanna (2014)

(untitled)
Introduction: This study evaluates the neonatal outcomes of elective caesarean section comparing before and after 39 weeks for term, uncomplicated singleton pregnancy. Elective caesarean section is a planned delivery in absence of labour and emergency deliveries due to specific maternal or fetal indication. Since there is evidence of increase risk in respiratory morbidity in the neonates that being delivered before 39 weeks, thus elective caesarean section is recommended to be done at 39 weeks or after for an uncomplicated singleton pregnancy. Objective: The aim of this study is to compare the neonatal outcomes in regards of delivery before 39 weeks and at 39 weeks and after; to evaluate the benefits and risk of delaying delivery in an elective caesarean section in Hospital Sultanah Nurzahirah, Kuala Terengganu. Methodology: A comparative cross sectional study conducted in period of a year time in 2012, involving recruitment of 312 patients through out the antenatal period, women with uncomplicated singleton pregnancy at term with an indication for elective caesarean section being included. They were divided into 2 groups, elective caesarean section before 39 weeks of gestation and elective caesarean section at and after 39 weeks of gestation; in which 156 patients per group. Data collected for demographic and outcomes measured involving both maternal and neonatal during and after the delivery till discharge. Results: Significant difference seen in numbers of admission, prolonged hospitalization, rates of neonatal respiratory morbidity and neonatal adverse outcomes comparing the two groups. Admission to neonatal care unit for the group before 39 weeks was 46/156 neonates (29.5%) whereas in the group at 39weeks and after was 17/156 neonates (10.9%) with p value<0.005. Prolonged hospitalization more than 48 hours for the group before 39 weeks was 30/156 neonates (19.2%) compared to the group at 39 weeks and after was 7/156 (4.5%) with p<0.005. The rates of neonatal respiratory morbidity were 19.2% (30/156 neonates) and 6.4% (10/156 neonates) in the group before 39 weeks and at 39 weeks and after group, respectively; with p=0.001. There were 24 cases (15.4%) of TTN and 6 cases (3.8%) of congenital pneumonia were noted in the group before 39 weeks. There were 8 cases (5.1%) of TTN and 2 cases (1.3%) of congenital pneumonia in 39 weeks or after group. There was no significant difference in mean Apgar score, mean umbilical cord blood analysis for pH, bicarbonate level and base excess between both groups. The other neonatal adverse outcomes measured were hypoglycaemic episodes, neonatal jaundice and other infections, which showed difference in numbers between these two groups. There were 2 cases of neonatal mortality in this study involve group less than 39 weeks. Conclusions: Elective caesarean section before 39 weeks were associated with increased risk of admission to neonatal care unit, prolonged hospitalization, neonatal respiratory morbidities and neonatal adverse outcome. Therefore, 39 weeks of gestation appears to be the ideal timing for elective cesarean delivery for uncomplicated singleton pregnancy.